2021
DOI: 10.3390/mi12080981
|View full text |Cite
|
Sign up to set email alerts
|

Towards Biohybrid Lung: Induced Pluripotent Stem Cell Derived Endothelial Cells as Clinically Relevant Cell Source for Biologization

Abstract: In order to provide an alternative treatment option to lung transplantation for patients with end-stage lung disease, we aim for the development of an implantable biohybrid lung (BHL), based on hollow fiber membrane (HFM) technology used in extracorporeal membrane oxygenators. Complete hemocompatibility of all blood contacting surfaces is crucial for long-lasting BHL durability and can be achieved by their endothelialization. Autologous endothelial cells (ECs) would be the ideal cell source, but their limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Further, endothelial proteins that reside on the endothelial cells (EC) will actively control hemostasis for optimized hemocompatibility [14]. For this approach, MHC silenced human cord blood derived ECs [15] and ECs derived from induced pluripotent stem cells (iPSC-ECs) [16] were identified as clinically relevant cell sources, which can be gained in sufficient numbers, while being immunologically invisible. Additional key findings within BHL development were the identification of potential surface coatings, enabling EC adhesion to the otherwise hydrophobic artificial material [17].…”
Section: Introductionmentioning
confidence: 99%
“…Further, endothelial proteins that reside on the endothelial cells (EC) will actively control hemostasis for optimized hemocompatibility [14]. For this approach, MHC silenced human cord blood derived ECs [15] and ECs derived from induced pluripotent stem cells (iPSC-ECs) [16] were identified as clinically relevant cell sources, which can be gained in sufficient numbers, while being immunologically invisible. Additional key findings within BHL development were the identification of potential surface coatings, enabling EC adhesion to the otherwise hydrophobic artificial material [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different studies demonstrated that the neo-endothelium, established on the HFM, remains viable, anti-thrombogenic, non-inflammatory and resilient under clinically relevant flow conditions that were simulated with endothelial cell culture medium even in long-term evaluation [ 14 , 17 ]. Furthermore, we identified two potential candidates for EC sources that could be safely applied for future clinical use of the BHL without the risk of acute rejection, i.e., ECs derived from induced pluripotent stem cells [ 21 ] and MHC-Class-I silenced human ECs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heparin and Albumin (H/A) coated and 1.8 × 3.2 cm (40 parallel aligned hollow fibers) sized patches were trimmed from the original HFM of the iLA membrane ventilator (Xenios, Heilbronn, Germany). After sterilization with ethylene oxide, the patches were endothelialized as described previously [ 21 ]. In brief, HFM patches were sandwiched between two custom made polycarbonate frames and three patches each were placed into a 50 mL syringe (B. Braun, Melsungen, Germany), which was filled with 23 mL EC suspension (9 × 10 5 ECs/mL in EGM2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is primordial that future advances in the research field focus on the development of better anticoagulant molecules and ECLS circuits that better mimic the physiologic conditions for extended ECLS use (79). Moreover, research in new ECLS bio-hybrid materials with the use of an endothelization technique is an important step toward the creation of complete biocompatible materials (79,(82)(83)(84)(85)(86).…”
Section: The Sign (+) Is Used As a Scale To Represent Circuit Priming...mentioning
confidence: 99%